Strategi Kepala Sekolah dalam Membentuk Karakter Islami Siswa di SD An-Nahl Kabupaten Lima Puluh Kota - Sri Fitra Oktrivia; Suswati Hendriani (Pusat Pengkajian dan Pengembangan Sumber Daya Manusia (P3SDM) Melati, 2023)
The purpose of this research is to describe and explain the principal's strategy in shaping the character of Islamic students and what factors support and hinder the formation of the character of Islamic students at An-Nahl Elementary School, Lima Puluh Kota District. The method used in this study is a qualitative approach to explore in-depth information about the strategies that have been carried out by the principal in shaping the character of Islamic students at An-Nahl Elementary School, Lima Puluh Kota District. Character education at An-Nahl Elementary School, Fifty Cities District includes nine main characters, namely honesty, trust, responsibility, cooperation, caring, independence, cleanliness, tidiness, and disciplined. The results of the study show that the principal has implemented good leadership. There are special characteristics in shaping the character of students at An-Nahl Elementary School, Fifty Cities District: a) people power, which is carried out through a command and prohibition or reward and punishment approach. b) Persuasive strategies are carried out by soliciting and forming input from the community and school members c) Normative re-education, namely educating and changing the paradigm of thinking of old school residents with new ones.